El Parlamento individual en un Parlamento de grupos : la participación en la función legislativa - García-Escudero Márquez, Piedad (Teoría y Realidad Constitucional, 2011)
This article examines how the Constitution and the Rulings of the Constitutional Court establish a concept of an individual Member or Parliament as the representative empowered with a parliamentary mandate as well as entitled to exercise the constitutional powers of the Chambers. This concept is then conforted to the rulers of the Standing Orders and the day-to-day parliamentary pratice in order to ascertain how these modify the Member´s scope of action and what parliamentary activities have in effect been «taken over» by Parliamentary Groups, wich are perceived as the central characters of the political game and the real initiators of almost all parliamentary proceedings in the Chambers. Se examina la concepción del parlamentario individual (supuesto autor, todavía titular del mandato representativo, del ejercicio de las funciones constitucionales de las Cámaras) que se obtiene de la Constitución y la jurisprudencia constitucional y compararla con la normativa contenida en los Reglamentos parlamentarios y con su aplicación práctica, para comprobar cuál es el ámbito de actuación que conserva aquél y cuál ha sido «usurpado» por los grupos parlamentarios, protagonistas del juego político y de la inmensa mayoría de las iniciativas e intervenciones en el seno de las Cámaras.